Judge Blaine Pettitt Retirement Luncheon at Fresno Hilton Hotel Ballroom - Watkins, Howard::::::::: (1985)
Lawrence J. O'Neill speaking at lectern, Judge Blaine Pettitt and Alice Pettitt seated at head table